Keunggulan karakteristik Serat Kenaf Sebagai Bahan Baku Kertas Kantong - Trismawati, Trismawati; Wikanaji, Darono; Prihatiningsih, Tri; Istifar, Vincent; Sunyoto, Andrik; Siswanto, Erik (Prosiding Seminar Nasional Sains dan Teknologi Terapan, 2024)
Kenaf (Hibiscus cannabinus) has long been known to the Indonesian people. The use of kenaf reached its peak during the Japanese occupation. Kenaf is not only used as bedding for livestock, but is also used to make rice cantons and sugar bags. Some known products include burlap sacks, carpets, ropes, geotextiles and handicrafts. This fiber is valued for its strength and multi-purpose function in producing environmentally friendly materials. In this study, the physical properties of kenaf fiber were compared with the physical properties of spruce wood fiber, which is known to have quite high physical fiber strength. Kenaf was cooked using soda process with 14% active alkali, the heating process time to reach a temperature of 160 oC was 1 hour and maintained at a cooking temperature of 160 oC for 2 hours at a pressure of 2.5 bar. The ratio of cooking liquid to kenaf fiber is 6. The research results show that the physical strength of kenaf fiber is comparable to the physical strength of spruce wood fiber and can be used as raw material for bag paper, for this reason it needs to be cultivated.